Steven universo e as expressões de subjetividades e corpos queer na animação infantil - Castro, Arthur Gomes de (2019)
The North-American cartoon Steven Universe was created by Rebecca Sugar and is broadcasted by Cartoon Network as well as having big TV ratings in comparison with other cartoons on the channel rost, it also recognized for being an example of inclusive media that shows a lot of diverse experiences that escapes some kind of norm. The main goal of this project is to understand how Steven Universe creates and disseminates inclusive ideals, demystifying and normalizing queer bodies and lifestyles, contrary to the traditional cartoons created by the norms of gender and sexuality. In order to do this, this project will work using the queer theory to discuss gender construction, especially on childhood, also will try to understand the possibilities of the animated medium, what its history, aesthetics and language can say about their primarily consumer and how it behaves within the commercial sphere that can shape its content